Survey of Association Between Indoor CO and CO2 Levels and Symptoms of Sick Building Syndrome Among Employees at Alang-Alang Lebar and Plaju Health Centers - Delviana; Agita Diora Fitri; Mariana (Sriwijaya Journal of Medicine, 2024)
Poor air quality and exceptionally high CO and CO2 pollutants can be contributing factors to Sick Building Syndrome (SBS). This study evaluated the relationship between individual factors and CO and CO2 levels with Sick Building Syndrome (SBS) symptoms in health center employees. 74 respondents work in the room of Alang-Alang Lebar and Plaju Health Center. Then, the respondents will fill out a questionnaire related to SBS symptoms. The rooms in the selected health centers will be measured for CO and CO2  levels. The results of filling out the questionnaire will be analyzed to determine whether SBS or not, and the results of measuring CO and CO2 levels will also be categorized as normal or not. Univariate and bivariate analyses related to individual employee factors, SBS symptoms, and CO and CO2. The results of 74 respondents showed that 36 respondents (48.6%) experienced SBS. The highest SBS symptoms were red, itchy, dry, or watery eyes (75%), and symptoms of dizziness or headache (71.4%). The highest CO level measurement result was seven ppm, the lowest was six ppm, while the highest CO2 level was 561 ppm, and the lowest was 498 ppm. These measurement results are still within the normal limits of the standards set. Bivariate test results showed that individual factors, CO and CO2, are not significantly related to SBS symptoms (p > 0.05).